2019
DOI: 10.1007/s10714-019-2597-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-Keplerian motion in Reissner–Nordström spacetime

Abstract: We present the analytical post-Newtonian solutions for the test particle's motion in the Reissner-Nordström spacetime. The solutions are formulated in the Wagoner-Will representation, the Epstein-Haugan representation, the Brumberg representation, and the Damour-Deruelle representation, respectively. The relations between the (post-)Keplerian parameters in different representations, as well as their relations to the orbital energy and angular momentum are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Hence, we need only to substitute the asymptotic forms (32) and Eq. ( 42) into the expansion (21) and then further expand these functions for large p. Although can be solved easily, their expressions are too lengthy to present here. Finally, substituting all these coefficients, as well as Eqs.…”
Section: F(u)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we need only to substitute the asymptotic forms (32) and Eq. ( 42) into the expansion (21) and then further expand these functions for large p. Although can be solved easily, their expressions are too lengthy to present here. Finally, substituting all these coefficients, as well as Eqs.…”
Section: F(u)mentioning
confidence: 99%
“…When determining the PS under pure gravity, most previous studies used essentially a type of PN approximation, i.e., they assumed that the trajectory is far from the center and close to an ellipse [14][15][16][17][18][19][20][21][22][23]. However, when the trajectory is close to the center, particularly when the center is a black hole, such as Sgr A * , high order results that were difficult to obtain using the PN approximation might be required to satisfy the required accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bini, Geralico and Ruffini have investigated the circular motion of a charged test particle in the field of the Reissner-Nordström black hole [38,39]. In our previous work, we have shown that the black hole's electric charge can contribute to the orbital perihelion precession at the 1PN order, but not to the orbital period at the same order [40]. It is interesting to further explore the effects of the black hole's charge on the particle's motion including the orbital perihelion precession and period at the higher PN orders.…”
Section: Introductionmentioning
confidence: 98%
“…Although the charged astronomical bodies have not been discovered, the possibility of their existence in the universe may not be ruled out. In fact, the charge effects of the astrophysical black holes and stars have been studied extensively [32][33][34][35][36][37][38][39][40][41]. For example, Bini, Geralico and Ruffini have investigated the circular motion of a charged test particle in the field of the Reissner-Nordström black hole [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [57,58], we have derived the quasi-Keplerian motion for the neutral test particle in the Reissner-Nordström spacetime, and that for the charged test particle.…”
Section: Introductionmentioning
confidence: 99%